THE TRIUMPH OF LIGHT OVER DARKNESS - Temirov Zafariddin; Xujanova Nasiba (Web of Journals Publishing, 2025)
This article explores the life and creative work of Islom Shoir Nazar ogli, a representative of the Narpay epic school. It analyzes the plot of the epic "Orzigul", performed by him, and its significance in the artistic legacy of the bakhshi tradition.
Keywords: Epic school, Islom Shoir, Herodotus, poet, epic, performance